Rapid decline of the geographically restricted and globally threatened Eastern Palearctic Lesser White-fronted Goose Anser erythropus - Ao, Peiru; Wang, Xin; Solovyeva, Diana; Meng, Fanjuan; Ikeuchi, Toshio; Shimada, Tetsuo; Park, Jinyoung; Gao, Dali; Liu, Guanhua; Hu, Binhua; Natsagdorj, Tseveenmyadag; Zheng, Bofu; et al. (Wildfowl, 2020)
The Lesser White-fronted Goose Anser erythropus, which breeds across northern Eurasia from Norway to Chukotka, is globally threatened and is currently classified as Vulnerable by the International Union for Conservation of Nature. The Eastern Palearctic population of the species was thought to breed in arctic Russia, from east of the Taimyr Peninsula to Chukotka, and to winter in East Asia, but its precise status, abundance, breeding and wintering ranges, and migration routes were largely unknown, reducing the effectiveness of conservation efforts. In this paper, we combined results from satellite tracking, field surveys, a literature review and expert knowledge, to present an updated overview of the winter distribution and abundance of Lesser White-fronted Geese in the Eastern Palearctic, highlighting their migration corridors, habitat use and the conservation status of the key sites used throughout the annual cycle. Improved count coverage puts the Eastern Palearctic Lesser White-fronted Geese population at c. 6,800 birds in 2020, which represents a rapid and worrying decline since the estimate of 16,000 in 2015, as it suggests at least a halving of numbers in just five years. East Dongting Lake (Hunan Province) in China is the most important wintering site for the species in East Asia, followed by Poyang Lake (Jiangxi Province) and Caizi Lake (Anhui Province), with one key wintering site in Miyagi County in Japan. Satellite tracking showed that eight individuals captured during summer on the Rauchua River, Chukotka, Russia wintered in the middle and lower reaches of the Yangtze River floodplain in China. Their migration speed was slower in spring than in autumn, mainly because of longer stopover duration at staging sites in spring. The tracked geese mainly used cultivated land on migration stopovers (52% in spring; 45% in autumn), tundra habitat in summer (63%), and wetlands (66%) in winter. Overall, 87% of the GPS fixes were in protected areas during the winter, far greater than in spring (37%), autumn (28%) and summer (7%). We urge more tracking of birds of differing wintering and breeding provenance to provide a fuller understanding of the migration routes, staging sites and breeding areas used by the geese, including for the birds wintering in Japan. The most urgent requirement is to enhance effective conservation and long-term monitoring of Lesser White-fronted Geese across sites within China, and particularly to improve our understanding of the management actions needed to maintain the species. Collaboration between East Asian countries also is essential, to coordinate monitoring and to formulate effective protection measures for safeguarding this population in the future.